HOW TO BETTER ENGAGE ONLINE STUDENTS WITH ONLINE STRATEGIES. - BRITT, DR. MARGARET (College Student Journal)
Online education is growing at a phenomenal rate. This growth in online education offers many opportunities to colleges and universities to reach students who may not have attended a traditional (brick and mortar) college or university. Online education also gives students more control over their education along with a more flexible schedule. As with every opportunity there comes a responsibility. For colleges and universities, this responsibility includes the need to effectively engage students in the online classroom to ensure learning. This paper will review the theories that can be used to foster online learning and education, as well as some of the best practices for effectively engaging the online student in the classroom. Don't despair -- these best practices do not require an investment in expensive technology or resources -- they just require the creativity and imagination of the instructor to redesign the learning experience and adapt it to the online platform. Authentic learning which includes the use of problems based on real world situations, scenarios and role playing exercises, case studies and problem based activities will be reviewed as one of the most effective ways to encourage engagement of the online student as well as their academic growth and development. As the paper discusses, these concepts can also be utilized with great success with the adult learner in the online classroom.